Preparation method of silicon-magnesium compound for thermal insulation material
Synthesis of silicon magnesium compounds by precipitation method solves the problems of low mechanical strength of silica aerogels and limited resources of traditional fiber materials, providing an environmentally friendly and easy mass production insulation material with high specific surface area and light bulk density.
Patent Information
- Application Number
- CN202510391552.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-07-25
AI Technical Summary
The existing silica aerogel has low mechanical strength and difficulty in forming large blocks. The traditional inorganic fiber material resources are limited and polluted the environment. The existing synthesis process is complex and costly, and cannot be mass-produced, making it difficult to meet the needs of environmental protection and insulation.
Sodium silicate and magnesium salt are used as raw materials to synthesize silicon magnesium compounds by precipitation method, control pH value and temperature, add amino silane coupling agent for surface modification, and obtain silicon magnesium compounds after aging, washing and pulverization.
The prepared silicon magnesium compound has high specific surface area, light bulk density and excellent thermal insulation properties. It is suitable for thermal insulation materials, and has a simple and easy industrialization process.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new thermal insulation materials, and particularly relates to a preparation method of a silicon-magnesium compound for thermal insulation materials. Background Art
[0002] Silica aerogel is a kind of low-density thermal insulation material. Its nano-scale pore size can significantly reduce gas heat conduction and convective heat transfer, making it an ideal "super insulation material" with broad application prospects in many fields such as aerospace, catalysis, and fuel cells. However, during the application process of silica aerogel, due to its extremely low density, its mechanical strength is low, it is difficult to form large-sized aerogel, and at temperatures above 800 °C, the pore structure collapses severely, resulting in a sharp decrease in its thermal insulation performance, which greatly limits the application of silica aerogel materials. How to improve the mechanical properties and thermal insulation performance of silica aerogel is of great practical significance for expanding the application of aerogel. Most aerogel thermal insulation products on the market use traditional inorganic fiber materials as the supporting materials for aerogel products, such as glass wool, slag wool, rock / asbestos, ceramic fiber cotton, etc.; however, the raw materials of these materials are increasingly depleted, and among traditional inorganic fiber materials, due to the stable performance of mineral fibers and their difficulty in degradation, they cause environmental pollution and do not meet the requirements of environmental protection. Currently, silica aerogel is generally synthesized from raw materials including silicon source, modifier, catalyst, ethanol, water and other raw materials, with complex processes, high production costs, and inability to achieve mass production, which restricts the development of the silica aerogel thermal insulation field. Therefore, it is urgent to find a new environmentally harmless material as the supporting material for new aerogel materials to meet the current multi-faceted requirements of environmental protection, fiber interface bonding strength, and thermal insulation.
[0003] Chinese Patent CN105837244A discloses an environmentally friendly magnesium silicate fiber felt reinforced silica aerogel composite material and its preparation method. The composite material is composed of a magnesium silicate fiber felt and silica aerogel; among them, the magnesium silicate fiber felt is the reinforcing body, with a content of 30-50% of the total mass of the sample, and the silica aerogel is the matrix. The silicon source material, absolute ethanol and deionized water are used to obtain the precursor Si(OH)4 of SiO2 aerogel, and then the preformed magnesium silicate fiber felt is used to prepare a magnesium silicate fiber reinforced SiO2 composite wet gel, which is then subjected to impurity ion replacement and high-temperature heat treatment to obtain a magnesium silicate fiber felt reinforced silica aerogel composite material. The process for synthesizing the magnesium silicate fiber felt reinforced silica aerogel composite material by this method is complex and not suitable for industrial production. Summary of the Invention
[0004] In view of the problems existing in the prior art, the present invention provides a preparation method of a silicon-magnesium compound for heat-insulating materials. The silicon-magnesium compound for heat-insulating materials prepared by the present invention has application performance in heat insulation that is basically close to that of silica aerogel.
[0005] The primary object of the present invention is to provide a preparation method of a silicon-magnesium compound for heat-insulating materials.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A preparation method of a silicon-magnesium compound for heat-insulating materials, comprising the following steps:
[0008] S1. Prepare water glass, sulfuric acid and magnesium salt solutions with certain concentrations;
[0009] S2. Under certain temperature conditions, add pure water, magnesium salt solution and part of the water glass solution, and then add a part of sulfuric acid to a certain pH to form a silicon-magnesium sol compound;
[0010] S3. After aging and stirring the silicon-magnesium sol compound in step S2, heat and react, adjust the pH to be alkaline, maintain this pH value and temperature, and add the remaining water glass and sulfuric acid at the same time. Then add an amino-silane coupling agent for surface modification and carry out an aging reaction. After aging at a second elevated temperature and pressure for a certain time, adjust the pH to be acidic, and then age to form a silicon-magnesium compound;
[0011] S4. Wash the silicon-magnesium compound obtained in step S3 with pure water, spray dry it, and then pulverize it by air flow to obtain the product.
[0012] Preferably, in step S1, the modulus of the water glass is 1.50 - 2.50, the silica concentration of the water glass solution is 5wt% - 15wt%, and the sulfuric acid concentration is 5wt% - 15wt%.
[0013] Preferably, in step S1, the magnesium salt is magnesium nitrate, magnesium chloride or magnesium sulfate, and the concentration of the prepared magnesium salt solution is 15wt% - 20wt%.
[0014] Preferably, in step S2, the magnesium salt concentration in the bottom liquid formed after adding pure water, magnesium salt solution and part of the water glass solution is 7wt% - 10wt%, and the sodium oxide concentration is 0.5wt% - 1.5wt%.
[0015] Preferably, the temperature condition in step S2 is 40 - 60°C.
[0016] Preferably, the addition amount of the water glass in step S2 is 25% - 30% of the total water glass amount.
[0017] Preferably, the amino silane coupling agent described in step S2 is one of γ-aminopropyltriethoxysilane (KH550), N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792), and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane (KH602).
[0018] Preferably, the addition amount of the amino silane coupling agent described in step S3 is 0.10 wt% to 0.50 wt% of the total silica content.
[0019] Preferably, in step S3, the pH is adjusted to an alkaline value of 8 to 10, the pH is adjusted to an acidic value of 1.0 to 3.0, the heating reaction temperature of the silica-magnesia sol compound is 40 to 60 °C, the secondary temperature and pressure aging temperature is 120 to 150 °C, and the pressure is 0.5 to 1.0 MPa.
[0020] The second object of the present invention is to provide a silica-magnesia compound for heat-insulating materials, which is prepared by the above method.
[0021] The third object of the present invention is to provide the use of the above silica-magnesia compound in the preparation of heat-insulating materials.
[0022] Preferably, the silica content of the silica-magnesia compound is 89 to 92%, the content of Mg element is 5 to 10%, the porosity is 1.50 cm 3 / g to 1.80 cm 3 / g, the bulk density is 0.15 g / cm 3 to 0.20 g / cm 3 and the specific surface area is 500 to 800 g / cm 2 .
[0023] The following is a detailed synthesis scheme of the silica-magnesia compound for heat-insulating materials:
[0024] Under the condition of a temperature of 40 to 60 °C, add to 5 m 3Add 1500 - 2000 L of pure water, 15 wt% - 20 wt% of magnesium salt solution, and water glass solution with a modulus of 1.50 - 2.50 and a concentration of 5 wt% - 15 wt% into the pressure reactor to prepare a bottom liquid with a magnesium salt concentration of 7 wt% - 10 wt% and a sodium oxide concentration of 0.5 wt% - 1.5 wt%. Stir at full speed for 10 - 30 minutes, then add sulfuric acid solution with a concentration of 5 wt% - 15 wt% into the reactor until the pH reaches 6 - 9, and the addition time is 10 - 30 minutes. Stop stirring after reaching the pH. After 3 - 5 minutes, a silica-magnesium sol compound is formed. After forming the silica-magnesium sol compound, react at a temperature of 40 - 60 °C for 20 - 40 minutes, and then disperse the silica-magnesium sol compound by stirring at full speed for 20 - 40 minutes. After the full-speed dispersion is completed, adjust the pH to 8 - 10 with a small amount of water glass, and raise the pressure of the reactor to 0.5 - 1.0 Mpa and the temperature to 120 - 150 °C. Then add water glass with a flow rate of 500 - 1000 L / h into the reactor for 30 - 60 minutes. While adding water glass, add sulfuric acid solution into the reactor and keep the pH of the reactor at 8 - 10. After adding the water glass, add an amino-functional silane coupling agent dispersed in ethanol with a silica content of 0.10 wt% - 0.50 wt%, and react and age at this pH condition for 90 - 120 minutes. After aging is completed, reduce the pressure of the reactor to atmospheric pressure, then add pure water to cool down to 70 - 90 °C, and then adjust the pH to 1.0 - 3.0 with sulfuric acid at this temperature condition for aging for 20 - 60 minutes. After aging is completed, pump it into a pressure filter plate and frame and wash it with pure water. The washing time is 3 - 6 hours, and wash until the conductivity is below 100 us / cm. After washing is completed, spray-dry the slurry and pulverize it by air flow to obtain the silica-magnesium compound for thermal insulation materials.
[0025] The silica-magnesium compound synthesized in this application has a large specific surface area, a high oil absorption value, a relatively light bulk density, a low thermal insulation and heat conduction rate, a strong compressive capacity, water absorption, and excellent fire resistance, and can be used for thermal insulation materials.
[0026] Compared with the prior art, the beneficial effects of the present invention are:
[0027] (1) This application uses magnesium nitrate, magnesium chloride, and magnesium sulfate as the magnesium source, sodium silicate as the silicon source, and the silica content of the silica-magnesium compound synthesized by the precipitation method is 89 - 92%, the content of Mg element is 5 - 10%, the porosity is 1.50 cm 3 / g - 1.80 cm 3 / g, the bulk density is 0.15 g / cm 3 - 0.20 g / cm 3 , and the specific surface area is 500 - 800 g / cm 2, this magnesium silicate compound has the characteristics of high specific surface area of silica aerogel, low bulk density, high pore volume, etc. At the same time, the magnesium content in this compound can reach 5-10%, and it can ensure that the compound has the performance in the field of thermal insulation similar to that of magnesium silicate compounds. The raw materials of this invention are simple and easy to obtain, and the synthesis process is simple, and industrial production can be easily realized.
[0028] (2) In this application, a magnesium silicate compound is synthesized using a silane coupling agent at 120-150°C and an aging pressure of 0.5-1.0 Mpa. Under certain temperature and pressure conditions, the amino silane coupling agent can increase the reaction rate between silicate ions and magnesium ions, and at the same time can accelerate the rapid growth of silica particles, enhancing the pore volume and specific surface area. Thus, the produced magnesium silicate compound has a large pore volume, high specific surface area, and good stability, which can further improve the durability, stability and other properties of the magnesium silicate compound in the field of thermal insulation. Specific embodiments
[0029] Next, the technical solutions of the magnesium silicate compound synthesized in this invention will be clearly and completely described in combination with the examples and comparative examples of this invention. Obviously, the described examples are only a part of the examples of this invention, rather than all the examples. Based on the examples in this invention, all other examples obtained by those of ordinary skill in the art without creative work fall within the scope of protection of this invention.
[0030] The test methods used in the following examples are all conventional methods unless otherwise specified; the materials, reagents, etc. used are all reagents and materials that can be obtained from commercial channels unless otherwise specified.
[0031] Example 1
[0032] A preparation method of a magnesium silicate compound for a thermal insulation material, comprising the following steps:
[0033] Under the condition of a temperature of 40°C, add to 5m 3Add 2000 L of pure water, a 15 wt% magnesium nitrate solution, and a water glass solution with a modulus of 2.50 and a silica concentration of 5 wt% to a pressure reactor to prepare a bottom liquid with a magnesium nitrate concentration of 7 wt% and a sodium oxide concentration of 1.5 wt%. Stir at full speed for 10 minutes, then add a 15 wt% sulfuric acid solution to the reactor until the pH reaches 6. The addition time is 30 minutes. Stop stirring after reaching the pH. A silicon-magnesium sol compound is formed after 3 minutes. After the formation of the silicon-magnesium sol compound, react at a temperature of 60 °C for 20 minutes. Then disperse the silicon-magnesium sol compound by stirring at full speed for 40 minutes. After the full-speed dispersion is completed, adjust the pH to 8 with a small amount of water glass. Raise the pressure of the reactor to 1.0 Mpa and the temperature to 120 °C. Then add water glass with a flow rate of 1000 L / h to the reactor for 30 minutes. While adding water glass, add a sulfuric acid solution to the reactor and maintain the pH of the reactor at 10. After adding the water glass, add γ-aminopropyltriethoxysilane (KH550) dispersed in ethanol with a silica content of 0.50 wt%. React and age at this pH condition for 120 minutes. After aging is completed, reduce the pressure of the reactor to atmospheric pressure, then add pure water to cool down to 70 °C. Then adjust the pH to 3.0 with sulfuric acid at this temperature condition and age for 20 minutes. After aging is completed, pump it into a filter press plate frame and wash it with pure water. The washing time is 3 hours, and wash until the conductivity is below 100 μs / cm. After washing is completed, spray-dry the slurry and pulverize it by air flow to obtain the silicon-magnesium compound for thermal insulation materials.
[0034] Example 2
[0035] A preparation method of a silicon-magnesium compound for thermal insulation materials, comprising the following steps:
[0036] Under the condition of a temperature of 40 °C, add to 5 m 3Add 1500 L of pure water, a 20 wt% magnesium chloride solution, and a water glass solution with a modulus of 2.50 and a silica concentration of 15 wt% to a pressure reactor to prepare a bottom liquid with a magnesium chloride concentration of 10 wt% and a sodium oxide concentration of 0.5 wt%. Stir at full speed for 30 minutes, then add a 15 wt% sulfuric acid solution to the reactor until the pH reaches 9. The addition time is 10 minutes. Stop stirring after reaching the pH. A silicon-magnesium sol compound is formed after 3 minutes. After the silicon-magnesium sol compound is formed, react at a temperature of 40 °C for 40 minutes. Then disperse the silicon-magnesium sol compound by stirring at full speed for 20 minutes. After the full-speed dispersion is completed, adjust the pH to 10 with a small amount of water glass. Raise the pressure of the reactor to 0.5 Mpa and the temperature to 150 °C. Then add water glass with a flow rate of 500 L / h to the reactor for 60 minutes. While adding the water glass, add a sulfuric acid solution to the reactor and maintain the pH of the reactor at 8. After the water glass is added, add N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792) dispersed in ethanol with a silica content of 0.10 wt%. React and age at this pH condition for 90 minutes. After the aging is completed, reduce the pressure of the reactor to atmospheric pressure, then add pure water to cool down to 90 °C. Then adjust the pH to 1.0 with sulfuric acid at this temperature condition and age for 60 minutes. After the aging is completed, pump it into a filter press plate frame and wash it with pure water. The washing time is 6 hours, and wash until the conductivity is below 100 us / cm. After the washing is completed, spray-dry the slurry and pulverize it by airflow to obtain the silicon-magnesium compound for thermal insulation materials.
[0037] Example 3
[0038] A preparation method of a silicon-magnesium compound for thermal insulation materials, comprising the following steps:
[0039] Under the condition of a temperature of 50 °C, add to 5 m 3Add 1800 L of pure water, a magnesium sulfate solution with a concentration of 16 wt%, and a water glass solution with a modulus of 2.00 and a silica concentration of 10 wt% into a pressure reactor to prepare a bottom liquid with a magnesium sulfate concentration of 8 wt% and a sodium oxide concentration of 1.0 wt%. Stir at full speed for 30 minutes, then add a 10 wt% sulfuric acid solution to the reactor until the pH reaches 7. The addition time is 20 minutes. Stop stirring after reaching the pH. A silicon-magnesium sol compound is formed after 4 minutes. After the formation of the silicon-magnesium sol compound, react at a temperature of 50 °C for 35 minutes, and then disperse the silicon-magnesium sol compound by stirring at full speed for 30 minutes. After the full-speed dispersion is completed, adjust the pH to 9 with a small amount of water glass. Raise the pressure of the reactor to 0.6 Mpa and the temperature to 130 °C. Then add water glass with a flow rate of 800 L / h to the reactor for 40 minutes. While adding water glass, add a sulfuric acid solution to the reactor and maintain the pH of the reactor at 9. After the water glass is added, add N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane (KH602), a silane coupling agent dispersed in ethanol with a silica content of 0.20 wt%. React and age at this pH condition for 100 minutes. After the aging is completed, reduce the pressure of the reactor to atmospheric pressure, then add pure water to cool down to 80 °C, and then adjust the pH to 2.0 with sulfuric acid at this temperature condition and age for 30 minutes. After the aging is completed, pump it into a pressure filter plate and frame and wash it with pure water. The washing time is 4 hours, and wash until the conductivity is below 100 us / cm. After the washing is completed, spray-dry the slurry and pulverize it by air flow to obtain the silicon-magnesium compound for thermal insulation materials.
[0040] Example 4
[0041] A preparation method of a silicon-magnesium compound for thermal insulation materials, comprising the following steps:
[0042] At a temperature of 45 °C, add to 5 m 3Add 1900 L of pure water, a magnesium sulfate solution with a concentration of 17 wt%, and a water glass solution with a modulus of 1.50 and a silica concentration of 12 wt% to a pressure reactor to prepare a bottom liquid with a magnesium sulfate concentration of 9 wt% and a sodium oxide concentration of 1.2 wt%. Stir at full speed for 20 minutes. Then add a sulfuric acid solution with a concentration of 12 wt% to the reactor until the pH reaches 8. The addition time is 30 minutes. Stop stirring after reaching the pH. A silicon-magnesium sol compound is formed after 4 minutes. After the formation of the silicon-magnesium sol compound, react at a temperature of 50 °C for 50 minutes. Then disperse the silicon-magnesium sol compound by stirring at full speed for 30 minutes. After the full-speed dispersion is completed, adjust the pH to 9 with a small amount of water glass. Raise the pressure of the reactor to 0.7 Mpa and the temperature to 140 °C. Then add water glass with a flow rate of 900 L / h to the reactor for 35 minutes. While adding the water glass, add a sulfuric acid solution to the reactor and maintain the pH of the reactor at 9.5. After adding the water glass, add the silane coupling agent N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane (KH602) dispersed in ethanol with a silica content of 0.30 wt%. React and age at this pH condition for 110 minutes. After aging is completed, reduce the pressure of the reactor to atmospheric pressure, add pure water to cool down to 85 °C, and then adjust the pH to 2.5 with sulfuric acid at this temperature condition and age for 40 minutes. After aging is completed, pump it into a filter press plate frame and wash it with pure water. The washing time is 5 hours, and wash until the conductivity is below 100 us / cm. After washing is completed, spray-dry the slurry and pulverize it by air flow to obtain the silicon-magnesium compound for thermal insulation materials.
[0043] Example 5
[0044] A preparation method of a silicon-magnesium compound for thermal insulation materials, comprising the following steps:
[0045] At a temperature of 50 °C, add to 5 m 3Add 1900 L of pure water, a magnesium chloride solution with a concentration of 19 wt%, and a water glass solution with a modulus of 2.50 and a silica concentration of 10 wt% into a pressure reactor to prepare a bottom liquid with a magnesium chloride concentration of 8 wt% and a sodium oxide concentration of 1.0 wt%. Stir at full speed for 25 minutes, then add a sulfuric acid solution with a concentration of 9 wt% to the reactor until the pH reaches 8. The addition time is 20 minutes. Stop stirring after reaching the pH. A silicon-magnesium sol compound is formed after 3 minutes. After the formation of the silicon-magnesium sol compound, react for 20 minutes at a temperature of 50 °C. Then disperse the silicon-magnesium sol compound by stirring at full speed for 30 minutes. After the full-speed dispersion is completed, adjust the pH to 9 with a small amount of water glass. Raise the pressure of the reactor to 0.9 Mpa and the temperature to 150 °C. Then add water glass with a flow rate of 1000 L / h to the reactor for 30 minutes. While adding water glass, add a sulfuric acid solution to the reactor and maintain the pH of the reactor at 10. After adding the water glass, add N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792) dispersed in ethanol with a silica content of 0.40 wt%. React and age for 120 minutes under this pH condition. After aging is completed, reduce the pressure of the reactor to atmospheric pressure, then add pure water to cool down to 75 °C. Then adjust the pH to 2.0 with sulfuric acid at this temperature and age for 50 minutes. After aging is completed, pump it into a pressure filter plate and frame and wash it with pure water. The washing time is 4.5 hours, and wash until the conductivity is below 100 us / cm. After washing is completed, spray-dry the slurry and pulverize it by air flow to obtain the silicon-magnesium compound for thermal insulation materials.
[0046] Example 6
[0047] A preparation method of a silicon-magnesium compound for thermal insulation materials, comprising the following steps:
[0048] Under the condition of a temperature of 60 °C, add to 5 m 3Add 1800 L of pure water, a 20 wt% magnesium nitrate solution, and a water glass solution with a modulus of 2.00 and a silica concentration of 12 wt% to a pressure reactor to prepare a bottom solution with a magnesium nitrate concentration of 10 wt% and a sodium oxide concentration of 1.2 wt%. Stir at full speed for 20 minutes. Then add a 10 wt% sulfuric acid solution to the reactor until the pH reaches 9. The addition time is 25 minutes. Stop stirring after reaching the pH. A silicon-magnesium sol compound is formed after 4 minutes. After the formation of the silicon-magnesium sol compound, react at 60 °C for 30 minutes. Then disperse the silicon-magnesium sol compound by stirring at full speed for 30 minutes. After the full-speed dispersion is completed, adjust the pH to 9 with a small amount of water glass. Raise the pressure of the reactor to 0.8 Mpa and the temperature to 140 °C. Then add water glass with a flow rate of 1000 L / h to the reactor for 30 minutes. While adding the water glass, add a sulfuric acid solution to the reactor and maintain the pH of the reactor at 9. After adding the water glass, add γ-aminopropyltriethoxysilane (KH550) dispersed in ethanol with a silica content of 0.50 wt%. React and age at this pH for 140 minutes. After aging is completed, reduce the pressure of the reactor to atmospheric pressure. Then add pure water to cool down to 80 °C. Then adjust the pH to 3.0 with sulfuric acid at this temperature and age for 60 minutes. After aging is completed, pump it into a pressure filter plate and wash it with pure water. The washing time is 4.0 hours. Wash until the conductivity is below 100 μs / cm. After washing is completed, spray-dry the slurry and crush it by air flow to obtain the silicon-magnesium compound for thermal insulation materials.
[0049] Comparative Example 1
[0050] The difference compared with Example 1 is that no magnesium nitrate solution is added during the preparation process, and other experimental parameters and operations are the same as those in Example 1.
[0051] Comparative Example 2
[0052] The difference compared with Example 1 is that, add 2000 L of pure water, a 20 wt% magnesium nitrate solution, and a water glass solution with a modulus of 2.50 and a silica concentration of 5 wt% to a 5 m pressure reactor to prepare a bottom solution with a magnesium nitrate concentration of 12 wt% and a sodium oxide concentration of 1.5 wt%, and other experimental parameters and operations are the same as those in Example 1. 3 Add 2000 L of pure water, a 20 wt% magnesium nitrate solution, and a water glass solution with a modulus of 2.50 and a silica concentration of 5 wt% to a pressure reactor to prepare a bottom solution with a magnesium nitrate concentration of 12 wt% and a sodium oxide concentration of 1.5 wt%. Other experimental parameters and operations are the same as those in Example 1.
[0053] Comparative Example 3
[0054] The difference compared with Example 1 is that the silane coupling agent is replaced with γ-glycidoxypropyltrimethoxysilane (KH560) dispersed in ethanol with a silica content of 0.50 wt%, and other experimental parameters and operations are the same as those in Example 1.
[0055] Comparative Example 4
[0056] The difference compared with Example 1 is that instead of performing the operations of heating and pressurizing, the reaction is carried out at normal pressure of 100 °C, and other experimental parameters and operations are the same as those in Example 1.
[0057] Result Analysis
[0058] 1. Test methods and standards for the physical and chemical properties of the product:
[0059] (1) Specific surface area and pore volume test: TriStar II 3020, a fully automatic specific surface area and porosity analyzer made by Micromeritics;
[0060] (2) Silicon dioxide content: Dissolve silicon dioxide with hydrofluoric acid and then calculate by the differential method;
[0061] (3) Magnesium element content: Cuprizone separation - xylidyl blue II spectrophotometry;
[0062] (4) Bulk density test: Bulk density refers to the density obtained by dividing the powder mass by the volume V of the container occupied by the powder, also known as bulk density.
[0063] The physical and chemical properties of seven parallel products in Example 1 are shown in Table 1.
[0064] Table 1
[0065]
[0066] The test methods and standards for the physical and chemical properties of the products prepared in Examples 2 - 6 and Comparative Examples of the present invention are the same as those in Example 1, and the physical and chemical properties of the products are shown in Table 2.
[0067] Table 2
[0068]
[0069]
[0070] 2. Comparison of physical property indexes
[0071] Comparison of the physical property indexes of Example products 1, 3, 5 and Comparative Examples 1 - 4 of the magnesium silicate compound for thermal insulation materials prepared by the present invention with cabot P200 silica aerogel:
[0072] Test methods and standards for product application:
[0073] (1) Thermal conductivity at room temperature: Guarded hot plate method: used for calibrating reference samples or heat flux meters, standard GB / T 10294 - 2008;
[0074] (2) Compressive strength: Use the method of testing the rebound strength after making samples with the magnesium silicate compound;
[0075] (3) Water absorption: The dropping water method is adopted: Drop a drop of water on the silicon-magnesium compound, and use a stopwatch to record the time when the water drop is completely absorbed.
[0076] The result data is shown in Table 3 as follows:
[0077] Table 3
[0078]
[0079]
[0080] It can be seen from the 7 parallel product test data of Example 1 in Table 1 above that the physical indicators of the products produced according to the technical solution of the present invention are basically close, indicating that the production of this technical solution is stable.
[0081] As shown in Table 2 and Table 3, it can be seen from Comparative Example 1 that without adding magnesium nitrate solution, the silica content and pore volume in the comparative example are significantly increased, the specific surface area and bulk density are significantly decreased, and the magnesium content is almost none. This is mainly because the magnesium content is reduced without adding magnesium nitrate solution, and the corresponding silica content is further increased. Secondly, the pore volume of the silicon-magnesium compound in the example is significantly lower than that of silica. Therefore, the absence of magnesium salt results in an increase in pore volume and a significant decrease in bulk density and specific surface area. In terms of physical properties, the compressive strength of the thermal insulation material decreases and the thermal conductivity increases.
[0082] It can be seen from Comparative Example 2 that when the concentration of magnesium nitrate added to the reaction kettle is 12%, which exceeds the range defined by the present invention, the silica content in the comparative example is significantly decreased. The data shows that the magnesium content is basically about 10%, the pore volume is significantly decreased, and the specific surface area and bulk density are significantly increased. Since more silicon-magnesium compounds are synthesized in the comparative example, and the pore volume of the magnesium silicate compound is significantly lower than that of silica, the bulk density is further increased and the specific surface area is also correspondingly increased. In terms of physical properties, this leads to a significant increase in the normal temperature thermal conductivity, which will seriously affect its heat insulation and heat preservation effects.
[0083] By replacing γ-glycidoxypropyltrimethoxysilane (KH560) with the silane coupling agent in Example 1 in Comparative Example 3, there is little difference in the silica and magnesium content in the comparative example. The magnesium content is basically slightly lower than that in Example 1. The pore volume and specific surface area are significantly decreased, and the bulk density is significantly increased. The addition of the amino silane coupling agent in the example of the present invention helps to synthesize more silicon-magnesium compounds, strengthen the richness of the structure of the silicon-magnesium compound, and improve the adhesion between the silane coupling agent and inorganic silicon-magnesium. In terms of physical properties, the compressive strength, heat preservation and water absorption of the material are improved, while the epoxy-based silane coupling agent does not achieve this technical effect.
[0084] In Comparative Example 4, the aging reaction was carried out without temperature and pressure increase. The differences in the contents of silicon dioxide and magnesium in the comparative examples were not significant, and the magnesium content was slightly lower than that of Example 1. The specific surface area decreased significantly while the bulk density increased significantly. This was mainly because high temperature and high pressure were conducive to the formation of more silicon-magnesium compounds. Secondly, it enhanced the richness of the structure of the silicon-magnesium compounds, and the formed silicon-magnesium compounds had a relatively high specific surface area.
[0085] Comparing the physical and chemical property indexes of the products of Examples 1, 3, and 5 and Comparative Examples 1-4 with those of ordinary precipitated silica (the preparation method can refer to Patent CN105837244A) and cabot P200 silica aerogel, although there are differences in the physical and chemical indexes of the silicon-magnesium compounds synthesized by the method of the present invention and cabot P200 silica aerogel, the compressive strength, normal temperature thermal conductivity, water absorption, and combustibility in thermal insulation materials are close to those of cabot P200 silica aerogel, and the heat insulation performance is good, so it can be used in thermal insulation materials.
[0086] Obviously, the above-mentioned embodiments of the present invention are only examples for clearly explaining the technical solutions of the present invention, rather than limitations on the specific implementation manners of the present invention. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the claims of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A preparation method of a silicon-magnesium compound for a thermal insulation material, characterized in that, It includes the following steps: S1. Prepare sodium silicate, sulfuric acid and magnesium salt solutions; S2. Add water, magnesium salt and a part of sodium silicate solution at a certain temperature, and then add sulfuric acid to adjust the pH to form a silica-magnesium sol compound; S3. After aging and stirring the silica-magnesium sol compound in step S2, heat it for reaction, adjust the pH to be alkaline, maintain this pH value and temperature, and add the remaining sodium silicate and sulfuric acid. Add an amino silane coupling agent for surface modification and then carry out an aging reaction. After aging by secondary temperature increase and pressure increase, adjust the pH to be acidic, and then age to form a silica-magnesium compound; S4. Wash, dry and air-grind the silica-magnesium compound obtained in step S3 to obtain the product.
2. The preparation method of the silicon-magnesium compound for the thermal insulation material according to claim 1, characterized in that, In step S1, the modulus of the sodium silicate is 1.50 - 2.50, the concentration of silicon dioxide in the sodium silicate solution is 5wt% - 15wt%, and the concentration of the sulfuric acid is 5wt% - 15wt%.
3. The preparation method of the silicon-magnesium compound for the thermal insulation material according to claim 1, characterized in that, In step S1, the magnesium salt is magnesium nitrate, magnesium chloride or magnesium sulfate, and the concentration of the magnesium salt solution is 15wt% - 20wt%.
4. The preparation method of the silicon-magnesium compound for the thermal insulation material according to claim 1, characterized in that, In step S2, the addition amount of the sodium silicate is 25% - 30% of the total amount of sodium silicate.
5. The preparation method of the silicon-magnesium compound for the thermal insulation material according to claim 1, characterized in that, In the mixed solution formed by adding water, magnesium salt and a part of sodium silicate solution in step S2, the concentration of the magnesium salt is 7wt% - 10wt%, and the concentration of sodium oxide is 0.5wt% - 1.5wt%.
6. The preparation method of the silicon-magnesium compound for the thermal insulation material according to claim 1, characterized in that, In step S3, the amino silane coupling agent is one of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane.
7. The preparation method of the silicon-magnesium compound for a heat-insulating material according to claim 1, characterized in that, In step S3, the addition amount of the amino silane coupling agent is 0.10wt% - 0.50wt% of the total content of silicon dioxide.
8. The preparation method of the silicon-magnesium compound for the thermal insulation material according to claim 1, characterized in that, In step S3, the pH value adjusted to be alkaline is 8 - 10, the pH value adjusted to be acidic is 1.0 - 3.0, the heating reaction temperature of the silica-magnesium sol compound is 40 - 60°C, the secondary temperature increase and pressure increase aging temperature is 120 - 150°C, and the pressure is 0.5 - 1.0MPa.
9. Application of the silica-magnesium compound prepared by the method according to any one of claims 1 - 8 in the preparation of heat-insulating materials.
10. The application according to claim 9, wherein The silicon-magnesium compound contains 89-92% of silicon dioxide, 5-10% of Mg element, and has a porosity of 1.50 cm 3 / g - 1.80 cm 3 / g, a bulk density of 0.15 g / cm 3 - 0.20 g / cm 3 and a specific surface area of 500 - 800 g / cm 2 .
Citation Information
Patent Citations
Environment-friendly magnesium silicate fibrofelt-reinforced silica aerogel composite and preparation method thereof
CN105837244A